Modeling Lithium Transport and Electrodeposition in Ionic-Liquid Based Electrolytes - Li, Guanchen; Monroe, Charles W. (Frontiers in Energy Research, 2021)
Purely ionic electrolytes—wherein ionic liquids replace neutral solvents—have been proposed to improve lithium-ion-battery performance, on the basis that the unique microscopic characteristics of polarized ionic-liquid/electrode interfaces may improve the selectivity and kinetics of interfacial lithium-exchange reactions. Here we model a “three-ion” ionic-liquid electrolyte, composed of a traditional ionic liquid and a lithium salt with a common anion. Newman's concentrated-solution theory is extended to account for space charging and chemomechanical coupling. We simulate electrolytes in equilibrium and under steady currents. We find that the local conductivity and lithium transference number in the diffuse double layers near interfaces differ considerably from their bulk values. The mechanical coupling causes ion size to play a crucial role in the interface's electrical response. Interfacial kinetics and surface charge on the electrodes both affect the apparent transport properties of purely ionic electrolytes near interfaces. Larger ionic-liquid cations and anions may facilitate interfacial lithium-exchange kinetics.